Estimation of Tap Water Quality in Babylon Governorate /Iraq, (2017) in Accordance with CCME - Ali Hammood, Zahraa; Jassim Mahan, Elaf; Kadhim Tayyeh, Halah (International Journal of Engineering and Technology, 2018)
This research included evaluation quality of water by utilizing Canadian Council of Ministers of the Environment Water Quality Index (CCME WQI) by analyzing many chemical and physical properties of tap water (inside houses) for five regions (AL Musayab, AL Kasim, AL kifil, AL Mahawil and Hilla Center) in Babylon Governorate, Iraq. The properties included (PH, temperature, Ec, Hardness, turbidity, T.D.S, Ca, So4, Mg) through three months (January, February, and March) / 2017. The evaluated amounts of CCME WQI proved that the quality of water round five regions were good through study interval and calculated amounts of properties were in Iraqi standards of drinking water (No. 417,2001) except Ca and turbidity.Â Â Â